2022
DOI: 10.1039/d1sc05791j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and computational evaluation of bicyclooctadienes towards molecular solar thermal energy storage

Abstract: Molecular solar-thermal energy storage (MOST) systems are based on photoswitches that reversibly convert solar energy into chemical energy. In this context, bicyclooctadienes (BOD) undergo a photoinduced transformation to the corresponding...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 41 publications
(69 reference statements)
0
37
0
Order By: Relevance
“…Furthermore, the systems have relatively long thermal back reaction times. However, we have recently reported that the storage energy can be significantly increased by altering the bridging unit of the NBD/QC system, a line of thought, which we will expand upon here. , …”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the systems have relatively long thermal back reaction times. However, we have recently reported that the storage energy can be significantly increased by altering the bridging unit of the NBD/QC system, a line of thought, which we will expand upon here. , …”
Section: Introductionmentioning
confidence: 91%
“…More specifically, we focus on scrutinizing the effects by elongating the bridging unit and on introducing heteroatoms. Our recent theoretical and experimental investigations have shown that elongating the bridge by a single carbon atom to obtain bicyclooctadiene (BOD) resulted in a 2–3-fold increase in the energy storage density of the system. , This increase in storage energy is likely to be caused by increased strain in the ring systems of the tetracyclooctane (TCO) photoproduct for which the bridging unit, contrary to the BOD, adopts a staggered conformation. The increased storage energy comes without compromising the linear optical properties, yet the thermal back reaction barriers were significantly reduced relative to the NBD/QC analogues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular solar thermal (MOST) systems have been recognized as a promising avenue to harvest and store thermal energy. [10][11][12][13][14][15] In the charging process, a stable isomer of a photochromic molecule absorbs photon energy and is converted into a high-energy metastable isomer, thereby storing solar energy in chemical bonds. The MOST system is discharged when the metastable isomer switches back to the stable isomer by external stimuli, with the release of stored energy in the form of heat.…”
Section: Introductionmentioning
confidence: 99%
“…MOST materials isomerize from a thermodynamically stable structure to a metastable structure, storing the absorbed energy in strained chemical bonds. Many organic molecules have been investigated for MOST applications, such as azobenzene, 16,[22][23][24] anthracene, 25,26 tetracarbonyl-fulvalene-diruthenium, [27][28][29][30] dihydroazulene/vinylheptafulvene (DHA/VHF), [31][32][33][34] bicyclooctadiene/tetracyclooctane (BOD/TCO) 35,36 and norbornadiene/quadricyclane (NBD/QC). [37][38][39][40][41][42][43] The NBD/QC system is one of the top candidates, where the NBD undergoes a [2+2]-photocycloaddition to the photoisomer QC (Figure 1).…”
Section: Introductionmentioning
confidence: 99%